2016
DOI: 10.1128/aac.01139-16
|View full text |Cite
|
Sign up to set email alerts
|

Stringent Response Factors PPX1 and PPK2 Play an Important Role in Mycobacterium tuberculosis Metabolism, Biofilm Formation, and Sensitivity to Isoniazid In Vivo

Abstract: g Mycobacterium tuberculosis remains a global health threat largely due to the lengthy duration of curative antibiotic treatment, contributing to medical nonadherence and the emergence of drug resistance. This prolonged therapy is likely due to the presence of M. tuberculosis persisters, which exhibit antibiotic tolerance. Inorganic polyphosphate [poly(P)] is a key regulatory molecule in the M. tuberculosis stringent response mediating antibiotic tolerance. The polyphosphate kinase PPK1 is responsible for poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(80 citation statements)
references
References 79 publications
(122 reference statements)
3
77
0
Order By: Relevance
“…Though its applicability to B . burgdorferi has been controversial (Wormser and Schwartz, ; Wormser et al ., ; Iyer et al ., ), persistence is a widely accepted phenomenon in microbiology which in some instances can have therapeutic implications (Dahl et al ., ; Lewis, ; Amato et al ., ; Zhang, ; Putrins et al ., ; Brauner et al ., ; Chuang et al ., ; Corrigan et al ., ). Persisters, while non‐dividing, appear to be metabolically active (Michiels et al ., ).…”
Section: Could the Borrelial Stringent Response Mediate Antimicrobialmentioning
confidence: 99%
See 1 more Smart Citation
“…Though its applicability to B . burgdorferi has been controversial (Wormser and Schwartz, ; Wormser et al ., ; Iyer et al ., ), persistence is a widely accepted phenomenon in microbiology which in some instances can have therapeutic implications (Dahl et al ., ; Lewis, ; Amato et al ., ; Zhang, ; Putrins et al ., ; Brauner et al ., ; Chuang et al ., ; Corrigan et al ., ). Persisters, while non‐dividing, appear to be metabolically active (Michiels et al ., ).…”
Section: Could the Borrelial Stringent Response Mediate Antimicrobialmentioning
confidence: 99%
“…The term 'bacterial persistence' is used to describe the ability of pathogenic bacteria ('persisters') to survive in infected host tissues despite the presence of effective levels of antimicrobials and antibacterial cellular and humoral immunity (Lewis, 2010;Nguyen et al, 2011;Balaban et al, 2013;Conlon et al, 2015;Michiels et al, 2016). Though its applicability to B. burgdorferi has been controversial (Wormser and Schwartz, 2009;Wormser et al, 2012;Iyer et al, 2013), persistence is a widely accepted phenomenon in microbiology which in some instances can have therapeutic implications (Dahl et al, 2003;Lewis, 2010;Zhang, 2014;Putrins et al, 2015;Brauner et al, 2016;Chuang et al, 2016;Corrigan et al, 2016).…”
Section: The Stringent Response and B Burgdorferi Residence In Vertementioning
confidence: 99%
“…Intracellular polyP levels are known to be important for maintaining susceptibility to INH (Thayil et al ., ; Chuang et al ., ; Wakamoto et al ., ; Chuang et al ., ) and some other anti‐tuberculosis drugs (Singh et al ., ). However, a recent study has shown that accumulation of polyP in mycobacteria increased susceptibility to β‐lactams and clofazimine (Chuang et al ., ). We do not know why polyP has different actions in controlling susceptibility to different drugs.…”
Section: Discussionmentioning
confidence: 98%
“…At day 0, 10 6 macrophages were infected with 5x10 6 of logarithmically growing H37Rv bacilli. The cells were harvested 4 days after infection, RNA was extracted and qPCR analysis was performed, as described previously [19]. The primers were listed in Table 1.…”
Section: Ic-21 Macrophages Infection and Real-time Pcr Analysismentioning
confidence: 99%
“…Although the Mtb stringent response contributes to the formation of persisters and antibiotic tolerance, it remains to be determined whether this pathway can be targeted therapeutically during chronic Mtb infection. We have shown previously that DNA vaccination with four key stringent response genes (relMtb, sigE, ppk2, and ppx1) generated antigen-specific CD4 + T-cell responses and vaccination prior to Mtb aerosol challenge augmented the tuberculocidal activity of isoniazid in mice [19]. However, very limited data are available regarding antigen presentation of stringent response factors during antitubercular treatment in vivo, as well as the optimal target for therapeutic DNA vaccination, which is an effective strategy for generating cellular and humoral immunity in various diseases [20].…”
Section: Introductionmentioning
confidence: 99%